HEALTHY LIFESTYLE - Shokirova Mohina Erkinovna (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract : A healthy lifestyle is essential for promoting physical, mental, and social well-being. Modern societies face increasing challenges due to urbanization, sedentary behaviors, and technological dependence, which contribute to chronic diseases such as obesity, cardiovascular disorders, and depression. This study explores the role of balanced nutrition, regular physical activity, and mental health practices in enhancing overall human health. Evidence-based interventions and recommendations are provided to support sustainable healthy habits. The findings emphasize the importance of integrated approaches that combine dietary guidance, exercise routines, and psychological support to improve quality of life and prevent non-communicable diseases.